Clinical pathway for moderate to severe acute bacterial skin and skin structure infections from a US perspective: a roundtable discussion. Issue 4 (7th August 2016) - Bosso, John A.; Casapao, Anthony M.; Edwards, Jonathan; Klinker, Kenneth; McCoy, Christopher; Nicolau, David P.; Perez, Katherine K.; Marcarelli, Andrew; Dua, Deeksha
ABSTRACT: This article was written with the aim to establish a consensus clinical pathway for long-acting lipoglycopeptide antibiotics such as oritavancin (Orbactiv®) and dalbavancin (Dalvance®) for the treatment of acute bacterial skin and skin structure infections (ABSSSI). Seven infectious diseases pharmacy specialists from a variety of facilities across the United States (US) participated in a roundtable discussion to consider the use of newer single-dose long-acting lipoglycopeptides, and integrate them into clinical pathways for ABSSSI. They identified two ways of treating with these drugs: first, to facilitate discharge from the hospital by switching from initial therapy (e.g., with intravenous (IV) vancomycin) and second, to avoid hospital admission altogether, since the product can be administered in several outpatient settings of care including the emergency department (ED), observation unit (OU) or outpatient infusion center. The participants used existing literature on classification and treatment of ABSSSI and their experience in the clinical setting as bases for their discussion and came to a consensus on the considerations for patient inclusion and exclusion as well as a pathway for outpatient treatment with long-acting lipoglycopeptides. As a result of the discussion, we concluded that the current treatment paradigm for ABSSSI is ripe for re-evaluation and reconfiguration in order to more closely align with the changing healthcare landscape. Hospital stakeholders are constantly searching for new strategies that can improve quality of care while simultaneously reducing overall expenses. The availability of single-dose long-acting lipoglycopeptides is an opportunity to opt for lower-cost outpatient treatment of appropriate ABSSSI patients. This article proposes the inclusion and exclusion considerations, along with a consensus treatment pathway, that could provide a solid foundation for facilities to construct and adapt their own effective clinical pathways for ABSSSI.